Strengthening practice readiness through a pediatric critical care elective: A pre–post evaluation - Vickey Keathley; Anne Derouin; Jacqui McMillian Bohler; Lisa Lewis; Remi Hueckel; Amanda Hodges; Julie A. Thompson (Journal of Nursing Education and Practice, 2026)
Background and objective: New graduate nurses frequently report gaps in confidence, self-efficacy, and readiness for high-acuity pediatric practice, largely due to limited exposure to critical care environments during prelicensure education. Specialty electives may offer an upstream strategy to strengthen preparation and support pediatric workforce development. This evaluation examined the impact of a pediatric acute–chronic critical care elective on prelicensure nursing students’ confidence, self-efficacy, and perceived readiness for high-acuity pediatric practice. Methods: A pre–post quality improvement design was used to evaluate a 12 week elective within an accelerated prelicensure program. Seventeen Likert scale items measured confidence, self-efficacy, and perceived readiness across pediatric critical care domains. Wilcoxon signed rank tests and effect sizes (r) were used to assess changes. Qualitative reflections from journals and discussion boards were analyzed using thematic content analysis to contextualize quantitative findings. Results: Eighteen students completed matched surveys. Statistically significant improvements were observed across all 17 domains, with large effect sizes (r = .588–.940). The greatest gains occurred in ventilator management (107.5%), pediatric emergency/code preparedness (76.5%), and recognition of pediatric shock (63.2%). Qualitative themes demonstrated increased confidence, strengthened self-efficacy, and clearer career trajectories. Students described greater decisiveness in high-acuity situations, improved application of structured communication frameworks, and the value of mentorship from pediatric and neonatal critical care nurses. Conclusions: Participation in the pediatric critical care elective was associated with meaningful improvements in students’ confidence, self-efficacy, and perceived readiness for high-acuity pediatric practice. Findings support specialty focused electives as feasible, scalable strategies to enhance practice readiness and contribute to pediatric workforce development.